Analisis Celebrity Endorser, Brand Image, Brand Trust Dan Iklan Televisi Terhadap Keputusan Pembelian Sampo Clear Di Toko Mapur Desa Jagalempeni Kabupaten Brebes - Mey Nur Aisyah; Citra Mega Suara; Ari Kristiana; Dumadi Dumadi; Nasiruddin Nasiruddin (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
In the era of rapid development of digital technology, one of the marketing strategies that is increasingly being applied is through artists as advertising promotions for a product through television, including advertisements on Clear shampoo products. The main objective of this study was to evaluate the effect of celebrity endorser analysis, brand image, brand trust and television advertising on shampoo purchase decisions at Mapur stores in Brebes District. The correlation method with the quantitative approach method carried out is based on positivistic research data (concrete data), namely numerical values that will be measured by statistics as a calculation test tool, related to the problem studied to produce a conclusion. The population of this study was Clear shampoo customers at the Mapur store, Jagalempeni Village, Brebes Regency. The sample was obtained by the Slovin formula with a margin of error of 10% of the population of 413 people, then a sample of 80 respondents was obtained. The research instrument used was in the form of primary data from filling out questionnaires. The results of the t test in the study found that the brand trust variable did not have a significant influence on purchasing decisions, brand trust had an effect on purchasing decisions, television advertisements did not affect purchase decisions. Based on the F test, this value is obtained that brand trust has the most significant influence, followed by brand image, television advertising, and celebrity endorsers in order of significance of influence in a given analysis model. These results provide an idea of the relative contribution of each independent variable to the dependent variable simultaneously influencing the determination in purchasing decisions on Clear shampoo products.